3 V operation of pentacene-based floating-gate memory realized by the isolation process with Ar/N2-plasma nitridation for N-doped LaB6 metal and high-k LaBxNy insulator stacked structure. (1st April 2023) - Hong, Eun-Ki; Ohmi, Shun-ichiro
Abstract : In this paper, we have investigated the low-voltage operation of pentacene-based floating-gate (FG) memory utilizing nitrogen-doped (N-doped) LaB6 metal and LaB x N y insulator stacked structure. The pentacene-based FG Au/pentacene/N-doped LaB6 (Metal: M)/LaB x N y (Insulator: I)/N-doped LaB6 (M)/LaB x N y (I)/n + -Si(100) (Semiconductor: S) MIMIS organic field-effect transistor (OFET) was fabricated by utilizing the Ar/N2 -plasma nitridation to isolate the edge region of the N-doped LaB6 FG with Au source/drain (S/D) electrodes. The Ar/N2 -plasma nitridation was found to be effective in suppressing the leakage current between the Au S/D electrodes and N-doped LaB6 FG. The pentacene-based FG memory was successfully developed with the memory window (MW) of 0.71 V and the saturation mobility ( μ sat ) of 1.8 × 10 −2 cm 2 /(V·s), under pulse input of ±3.4 V/10 ms due to the small equivalent oxide thickness (EOT) of 3.1 nm. Furthermore, MW of 0.4 V was obtained under minimum program/erase pulse amplitude/width of ±3 V/100 μ s at the process temperature of 200 °C.